Molecular mechanisms of macrophages adaptation when supplemented with phospholipids with Omega-3 and Omega-6 fatty acids - Maurício, Tatiana Sofia Cardoso (2023)
Macrophages are fundamental cells of the innate immune system, deeply involved in the immune response. These immune cells can express different phenotypes, with a key role in inflammation. The impact of polyunsaturated fatty acids (PUFAs) in the immune system has been extensively investigated in the last decades, particularly the effect of omega-3 (ω-3) and omega-6 (ω-6) fatty acids, in human health. Several studies have demonstrated that polyunsaturated fatty acids are intimately involved in the immune response, attributing an immunomodulatory effect to these substances. The present work provides a multi-omic analysis combining the analysis of the lipidome, the proteome and the metabolome of a macrophage cell line (RAW 264.7). In our study, we employed a liquid chromatography mass-spectrometry based approach (LC-MS), to identify and quantify the changes in the set of lipids, proteins and metabolites, in macrophages supplemented with two types of phospholipids containing omega-3 (PC 18:0/22:6) or omega-6 (PC 18:0/20:4) fatty acids, alone and in the presence of a pro-inflammatory agent, lypopolissacharide (LPS). In the lipidomic analysis, we identified and quantified 299 lipid species. Supplementation of macrophages with ω-3 and ω-6 phospholipids plus LPS, produced significant changes in the lipidome, with a marked increase in lipid species linked to the inflammatory response, enrolled in several pro-inflammatory signalling pathways. In the lipidomic analysis, these compounds also demonstrated a pro-resolving effect of inflammation. Regarding proteomic analysis, resulted in the identification of approximately 3000 proteins, with ω-3 and ω-6 phospholipids reprogramming the proteome of macrophages and amplifying the immune response, by these cells, also promoting the expression of anti-inflammatory proteins. Finally, metabolomic analysis consisted in the identification of 103 metabolites, supplementation with both ω-3 and ω-6 phospholipid induced the expression of several metabolites with a pronounced anti-inflammatory effect. Overall, our data shows that supplementation of macrophages with omega-3 and omega-6 phospholipids, effectively modulates the lipidome, the proteome and the metabolome of these immune cells, affecting several metabolic pathways involved in the immune response, triggered by inflammation. The compounds in study, promoted an increase in the metabolism of macrophages, impairing the pro-inflammatory response in these cells. The results obtained by the 3 omic approaches were congruent, demonstrating the complex metabolic network underlying the activation of macrophages and the role of supplementation with phospholipids.